Glosa do wyroku Sądu Administracyjnego w Warszawie z 9 listopada 2012 r., sygn. II AK a 283/12 - Wróbel, Adam (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The author agrees with the analysed point of view of the Court of Appeal in Warsaw. He shares the views — expressed in the thesis of this judgement — that: a the provision of Art. 158 § 2 C.C., which specifies the intentional crime of brawl or beating with unintentional consequence in the form of grievous bodily harm, cannot be in coincidence real, relevant with the provision of Art. 156 § 1 C.C., which specifies the intentional crime of causing grievous bodily harm — because of the homogeneous, intentional subjective side of both these provisions; b for the identification and assumption of criminal intention of a direct perpetrator irrelevant are the assessments in the scope of subjective side of an offence committed by a direct perpetrator — because both subjective sides are independent of each other.
Keywords: art. 158 k.k.; art. 156 k.k.; ciężki uszczerbek na zdrowiu; przestępstwo nieumyślne